Hypersensitivity to Natural Rubber Latex Gloves among Albanian Dental Students: The Role of Exposure Duration - Bakiri, Alketa; Kraja, Dhimiter; Skenderaj, Skender; Mingomataj, Doris; Petrela, Elizana; Mingomataj, Çerçiz; Rama, Ariol; Mingomataj, Ervin Ç (International Journal of Medical and Health Sciences Research, 2017)
Latex allergy is a common occupational disease among healthcare workers who use latex gloves. The aim of the present study was to determine the prevalence of allergy to latex gloves among dental students and the role of exposure duration in latex allergy. In this prospective study, a total of 240 students completed a self-administered questionnaire aiming at providing information about glove, working habits, signs and symptoms related to glove use, precautions taken to minimize it, etc. The challenge and patch tests were performed through latex gloves, and skin prick test with commercial extracts. The questionnaire items and diagnostic tests revealed that one-fourth of subjects were suspicious for latex gloves hypersensitivity. Their mean value for skin reactions like contact urticaria, irritant or allergic dermatitis was between 10% and 14%, while for non-cutaneous symptoms the mean value was under 5%. The average latex exposure (in hours) is estimated to be about 214±71 (SE), with a maximum of 11500 hours. The correlation between studied variables and the time exposure to latex gloves revealed weak to moderate relations with respect to reported latex allergy, eczematous reactions, hand erythema after glove wearing, irritant reactions during wash/washout procedures, concentration oscillations during usage of latex gloves, or dyspnea attack during latex exposure. Due to the relationship between allergic reactions to latex gloves and some medical histories during school practice, it seems to be necessary to undergo pre-matriculation evaluation and periodic health surveillance of dental students.